Voice of EFL mentor teachers: Mentorship for mutual professional development. - Firima Zona Tanjung; Bachrudin Musthafa; Yanty Wirza (Universitas Syiah Kuala, 2021)
This study aimed to report the voice of mentor teachers towards pre-service English teachers’ professional development viewed from relational, developmental, and contextual components during school teaching practice programs. The study employed a descriptive case study. Utilizing the purposive sampling technique, four mentor teachers from public and private junior secondary schools participated in this study. The instrument used was an interview protocol, and the data were collected through a one-on-one interview using a voice recorder for gathering a comprehensive perspective towards the pre-service English teachers’ professional learning. The data were analyzed by using a coding system and employing coding cycles. The findings showed that all components—relational, developmental, and contextual—were found. The mentor teachers voiced their perspective and stressed the developmental component because they found that the pre-service English teachers experienced hindrances both externally and internally regarding teaching performance, classroom management, and motivation. These hindrances contribute to their professional development. This present study result implies a policy implementation related to the synchronization between collaborating schools and universities. The synchronization can be in terms of preparing the mentor teachers and providing the pre-service English teachers a supportive mentorship. Furthermore, the collaboration between schools and universities is also required in the exchange of valuable sources concerning educational instruction trends such as evidence-based practices in peripheral contexts, English teaching for students with diverse cultural backgrounds and academic competencies, and dissemination of best practices that have been implemented in schools for the formulation of teaching theories being taught through course subjects at teacher education departments in the universities.